EVALUATION METHOD OF JET AIRCRAFT FUEL CORROSION ACTIVITY UNDER DYNAMIC CONDITIONS - V. V. Kondratenko; I. M. Nikitin; V. V. Suzikov (Научный вестник МГТУ ГА)
A new evaluation method of jet aircraft fuel corrosion activity in the condition of flowing the rotable unit over with circulative fuel is presented in this article. The flow sheet for implementation of this method and preliminary results from the tests of jet fuel corrosion activity are introduced.